Gender representation, stereotypes, and bias in English Language textbooks: A systematic review of cross-country studies - Ankur Nandi; Tarini Hader; Tapash Das (An-Nisa’ Journal of Gender Studies, 2024)
English language textbooks play a crucial role in shaping students’ gender perceptions. However, they often reproduce stereotypes and biases through linguistic, visual, and activity-based representations. Although the awareness regarding this issue has been increasing, cross-country evidence on how textbooks sustain gender norms remains fragmented, necessitating a systematic review to support gender-sensitive education. This study examines how textbooks reproduce gender norms through linguistic, visual, professional, and leisure activity representations, and how cultural and regional contexts mediate gender bias and student perceptions. Using a Systematic Literature Review (SLR), 358 articles were screened and, 45 met the inclusion criteria. Cross-country thematic analysis revealed patterns of gender stereotypes, linguistic and visual biases, and the influence of cultural and institutional contexts. There are three main findings in this study. First, the interaction of linguistic, visual, professional, and non-formal activity aspects simultaneously constructs gender stereotypes in textbooks. Second, cultural context and education policy are shown to mediate gender bias. Third, strategies for developing gender-sensitive textbooks require a holistic approach to textbook revision, as well as diversification of academic publication channels. This study concludes that gender bias is systemic and multidimensional, shaped by language, visual, professional, and non-formal interactions and mediated by culture and policy, requiring holistic revision, mixed methods, and multi-database research. This study contributes a quadrant interaction model of gender representation and provides holistic policy recommendations, including textbook revision, strengthening mixed-methods research, multi-database searching, training, gender audits, and cross-country research networks.